Basic human values drive food choice decision-making in different food environments of Kenya and Tanzania - Blake, C.E.; Monterrosa, Eva C.; Rampalli, Krystal K.; Khan, A.N.S.; Reyes, L.I.; Drew, S.D.; Domínguez-Salas, Paula; Bukachi, S.A.; Ngutu, M.; Frongillo, Edward A.; Iruhiriye, Elyse; Girard, Amy W. (Elsevier, 2023)
Increased access to a variety of foods in low-and-middle-income countries (LMICs) has led to greater autonomy in food choice decision-making. Autonomy allows individuals to make decisions through negotiation of considerations in ways that are consistent with basic values. The aim of this study was to identify and describe how basic human values drive food choice in two diverse populations with transitioning food environments living in the neighboring East African countries of Kenya and Tanzania. Secondary data analysis was carried out on focus group discussions conducted with men and women in Kenya (n = 28) and Tanzania (n = 28) as part of prior studies on food choice. A priori coding based on Schwartz's theory of basic human values was conducted, followed by a narrative comparative analysis, which included review by original principal investigators. Values of conservation (security, conformity, tradition), openness to change (self-directed thought and action, stimulation, indulgence), self-enhancement (achievement, power, face), and self-transcendence (benevolence-dependability and -caring) were prominent drivers of food choice in both settings. Participants described how values were negotiated and highlighted existing tensions. For example, the value of tradition was cited as important in both settings but changing food contexts (e.g., new foods, diverse neighborhoods) increased prioritization of values like stimulation, indulgence, and self-directed thought and action. The application of a basic values framework was useful for understanding food choice in both settings. A focused understanding of how values drive food choice decision-making in the context of changing food availability in LMICs is essential for the promotion of sustainable healthy diets.